12.2k views
4 votes
Simplify by combining like
terms:
3(4x + 5) + 2

User Harrakiss
by
5.3k points

2 Answers

1 vote

Answer: 12x + 17

Explanation:

First, distribute the 3 to the values within the parentheses.

3 * 4x = 12x

3 * 5 = 15

The expression now becomes 12x + 15 + 2. Now you can combine like terms by adding 15 and 2, since they both have no variable.

12x + 15 + 2

12x + 17

Therefore, the final answer is 12x + 17.

User Michael Peterson
by
5.0k points
3 votes

Answer:

12x + 17

Explanation:

3(4x + 5) + 2 use the distributive property: a(b + c) = ab + ac

= (3)(4x) + (3)(5) + 2

= 12x + 15 + 2 combine like terms

= 12x + (15 + 2)

= 12x + 17

User Jashira
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.